Adobe Flash CS3 professional bible - Reinhardt, Robert 1973-; Dowd, Snow (Wiley Pub., 2007)
"Two of the savviest Flash experts in the industry show you how to add impact to your Web content. Robert Reinhardt and Snow Dowd know all the techniques and tricks, and they take you under the hood in this one-stop total reference guide to Flash CS3 Professional. Follow their tutorials, learn from cool examples, and discover insider secrets you won't find in any other book. Don't miss the special 16-page color insert loaded with spectacular examples"--Resource description page
Title from title screen. - Includes index
Keywords: Flash (Computer file); Computer animation; Interactive multimedia; Web sites -- Design; Flash (Computer software); Animation par ordinateur; Multimédias interactifs; Sites Web; Conception; computer animation; COMPUTERS; Digital Media; Video & Animation; Multimedia systems; Web sites; Design; Flash CS3 Professional